MODELING, ADME SCREENING & QSAR STUDIES ON FACTOR-XA INHIBITORS - SIBI NARAYANAN,; D. VELMURUGAN, (International Journal of Pharma and Bio Sciences, 2014)
Thromboembolic disease is caused by improper functioning of the blood coagulation process. The serine protease Factor Xa plays a central role in the coagulation cascade. FXa inhibitors have been identified to maintain a patient’s blood level within the therapeutic range and also shown to activate clotting over a much wider concentration range than thrombin in invitro assays. Predicting the binding structure of substrate in its receptor (docking simulation) is an effective way, which is used successfully in many applications. Novel and orally active FXa inhibitors incorporating 6-chloro-N-[(3S)-1substituted-2-oxo-3-pyrrolidinyl]-2-napthalenesulfonamides presented here exhibit good anticoagulant and antithrombotic properties. An ADME (Absorption, Digestion, Metabolism and Excretion) screening was done for second-generation potent drug development. Further, QSAR (Quantity Structure Activity Relationship) activity was also tested using Schrödinger Suite 2009. Insilico analysis proved that compound 1F can be used as a lead compound for the anti-coagulant and anti-inflammatory pathways.